«Galeotto fu’l libro e chi lo scrisse»: Literature as a Road to Hell - Belmonte, Miguel Ángel (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
In Canto V of Inferno, one of the most universally known passages of the Divine Comedy, Dante hints at the corrupting force of literature as triggering Paolo and Francesca’s adultery. This scheme in which the literary becomes a reason for perdition reappears in such well-known cases as Don Quixote and others less well known, such as the Dickensian Nicodemus Boffin of Our Mutual Friend. These writers reveal in their works their concerns about an influence they simultaneously seek and fear over their readers. Their «books within books» can be interpreted as a vaccine with which the writer aims to provide the reader with the tools to protect themselves from the perverse effects of a literature interpreted in a more romantic fashion. We follow Renato Poggioli, John Freccero and René Girard to propose an anti-romantic interpretation that underlines the actuality of the moral architecture of the Divine Comedy and its influence on various classics of later modern literature.
Keywords: Dante; Francesca; Galleoto; Cervantes; Dickens; Girard; Desires; Hell; Imitation; Books